Small-Conductance Ca2+-Activated K+ Channel 2 in the Dorsal Horn of Spinal Cord Participates in Visceral Hypersensitivity in Rats - Song, Yu; Zhu, Jun-Sheng; Hua, Rong; Du, Lei; Huang, Si-Ting; Stackman, Robert W.; Zhang, Gongliang; Zhang, Yong-Mei (Frontiers in Pharmacology, 2018)
Visceral hypersensitivity is a highly complex and subjective phenomenon associated with multiple levels of nervous system and a wide range of neurotransmission. The dorsal horn (DH) in spinal cord relays the peripheral sensory information into the brain. Small conductance Ca2+-activated K+ (SK) channels regulate neuronal excitability and firing by allowing K+ to efflux in response to increase in the intracellular Ca2+ level. In this study, we examined the influence of SK2 channels in the spinal DH on the pathogenesis of visceral hypersensitivity induced by colorectal distension (CRD) in rats. Electrophysiological results showed that rats with visceral hypersensitivity presented a decrease in the SK channel-mediated afterhyperpolarization current (IAHP), and an increase in neuronal firing rates and c-fos positive staining in the spinal DH. Western blot data revealed a decrease in the SK2 channel protein in the membrane fraction. Moreover, intrathecal administration of the SK2 channel activator 1-EBIO or CyPPA alleviated visceral hypersensitivity, reversed the decrease in IAHP and increased in neuronal firing rates in spinal DH in rats that experienced CRD. 1-EBIO or CyPPA effect could be prevented by SK2 channel blocker apamin. CRD could induce an increase in c-Fos protein expression in the spinal DH, which could be prevented by 1-EBIO. Together, these data suggest that visceral hypersensitivity and pain is associated with a decrease in the number and function of membrane SK2 channels in the spinal DH. Pharmacological manipulation of SK2 channels may open a new avenue for the treatment of visceral hypersensitivity and pain.